The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1002/jmor.1052080203
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional architecture of identified cerebral neurosecretory cells in an insect

Abstract: The organization of identified neurosecretory cell groups in the larval brain of the tobacco hornworm, Manduca sexta, was investigated immunocytologically. Computer-assisted three-dimensional reconstruction was used to examine the architecture of the neurosecretory cell groups. The group III lateral neurosecretory cells (L-NSC-III) which produce the prothoracicotropic hormone are located dorsolaterally in the protocerebrum and extend axons medially that decussate to the contralateral lobe prior to exiting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The axons of the A-cells first exit towards the anterior and then cross over to the opposite side, and pass in posterior direction until they leave the brain from the posterior side. Recently, a similar pathway has been described using confocal microscopy in the larval brain of the tobacco hornworm Manduca sexta [27]. We particularly noted the presence of large amounts of CCK-like material in the walls of the aorta adjacent to the CC-CA complex, but never in the glands themselves of Spilostethus.…”
Section: Electron Dense Materials Is Occasionally Associated With Golgsupporting
confidence: 78%
“…The axons of the A-cells first exit towards the anterior and then cross over to the opposite side, and pass in posterior direction until they leave the brain from the posterior side. Recently, a similar pathway has been described using confocal microscopy in the larval brain of the tobacco hornworm Manduca sexta [27]. We particularly noted the presence of large amounts of CCK-like material in the walls of the aorta adjacent to the CC-CA complex, but never in the glands themselves of Spilostethus.…”
Section: Electron Dense Materials Is Occasionally Associated With Golgsupporting
confidence: 78%
“…1B). The number, location, and projections of these neurons identify them as type II neurosecretory cells (Nihjout, 1975; Westbrook et al, 1991). In some preparations, a pair of weakly stained neurons was revealed lateral to the dorsal–posterior midline in the expected location of type III neurosecretory cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of a potentially prothoracicotropic peptide in the brain-retrocerebral complex and the ventral ganglia of honey bee (Apis mellifera) larvae and pupae corresponded to the reactivity to an antibody raised against the 30-kDa PTTH of the silkworm, Bombyx mori (Mizoguchi et al, 1990 (Westbrook et al, 1991, and with the corresponding neurons in Bombyx mori (Mizoguchi et al, 1990) is suggested by their localization within the brain, as well as by the fact that they are the only neurons in the dorsal protocerebrum that continually produce a PTTH-like peptide. Timing of appearence of this peptide in the dorsolateral neurons, coincides with increases in the hemolymph ecdysteroid titer (Rachinsky et al, 1990), as well as in prothoracic gland activity in honey bee larvae (Hartfelder, 1993 (Zitnan et al, 1993), and by the recent three-dimensional models of Bombyx PTTH (Noguti et al, 1995 (Gray et al, , 1994 (Tublitz and Sylvester, 1990 .…”
Section: Resultsmentioning
confidence: 99%
“…has considerably improved our knowledge on the structural organization of these neurons in the neuroendocrine axis of insects (O'Brien et al, 1988;Mizoguchi et al, 1990;Westbrook et al, 1991;Goltzené et al, 1992;Zitnan et al, 1993;Dai et al, 1994), and advanced our understanding of the development of the insect central nervous system (Westbrook and Bollenbacher, 1990 (Bowen et al, 1984). This eventually postpones, apparently by glia-neuron signaling (Hartfelder et al, 1994) (Rachinsky et al, 1990), with differences in ecdysteroid titer reflecting a caste-specific program of prothoracic gland activity (Hartfelder, 1993).…”
Section: Immunocytochemical Identification Of Ptth-immunoreactive Celmentioning
confidence: 99%